District health information software 2 (DHIS2) as a decision support tool for Health service management: evidence from a nationwide study in bangladesh: DHIS2 for Health Service Management in Bangladesh (Journal of Preventive and Social Medicine, 2026)
Background: District Health Information Software 2 (DHIS2) is the world’s largest open-source health management information system, adopted in Bangladesh since 2011 for decentralized online reporting. While widely used, evidence on its scopes and utilities for decision-making by health managers remains limited. This study aimed to explore how DHIS2 is being applied as a decision support tool for health service management at the sub-district or Upazila level in Bangladesh.Methods: A nationwide convergent mixed-methods study was conducted among Upazila Health and Family Planning Officers (UH&FPOs) designated as Upazila or sub-district health managers in Bangladesh from January to December 2018. For the quantitative part, all (n = 482) UH&FPOs were included, and data were collected using a pre-tested semi-structured questionnaire distributed via official group email, with postal returns accepted where necessary. For the qualitative part, focus group discussions and key informant interviews were conducted with UH&FPOs to better understand their experiences and practices. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically analyzed.Results: Among 482 UH&FPOs approached, 428 responded, yielding a response rate of 88.8%. The mean age was 47.1 (±6.3) years; 93.9% were male, and 31.1% had received DHIS2 training. Most respondents reported satisfactory use of DHIS2 for maternal health (75.7%) and neonatal and child health service (68.9%) monitoring, as well as immunization service (86.2%). However, application was lower for inpatient preparedness (63.6%), major equipment management (47%), and referral tracking (58.2%). Importantly, nearly three-quarters (74%) of UH&FPOs reported that DHIS2 has made their managerial responsibilities easier. Training was significantly associated with higher use of DHIS2 for coordination meetings, planning, and supportive management functions (p < 0.05). Qualitative findings highlighted challenges of complex datasets, fragmented training, and over-reliance on statisticians, but also proposed expansions such as drug databases, laboratory service reporting, and financial reporting modules.Conclusion: DHIS2 is a valuable tool for health service management at the Upazila level in Bangladesh, though its decision-making potential remains limited by gaps in data-use capacity and functional coverage. Strengthening managers’ ability to use DHIS2 data, and expanding managerial modules could enhance its effectiveness as a national decision-support platform and support progress toward Sustainable Development Goal 3.JOPSOM 2025; 44(1): 4-17